Remarkable ancient divergences amongst neglected lorisiform primates. (15th June 2015) - Pozzi, Luca; Nekaris, K. Anne‐Isola; Perkin, Andrew; Bearder, Simon K.; Pimley, Elizabeth R.; Schulze, Helga; Streicher, Ulrike; Nadler, Tilo; Kitchener, Andrew; Zischler, Hans; Zinner, Dietmar; Roos, Christian
<x xml:space="preserve">Abstract</x> Lorisiform primates (Primates: Strepsirrhini: Lorisiformes) represent almost 10% of the living primate species and are widely distributed in sub‐Saharan Africa and South/South‐East Asia; however, their taxonomy, evolutionary history, and biogeography are still poorly understood. In this study we report the largest molecular phylogeny in terms of the number of represented taxa. We sequenced the complete mitochondrial cytochrome b gene for 86 lorisiform specimens, including ∼80% of all the species currently recognized. Our results support the monophyly of the Galagidae, but a common ancestry of the Lorisinae and Perodicticinae (family Lorisidae) was not recovered. These three lineages have early origins, with the Galagidae and the Lorisinae diverging in the Oligocene at about 30 Mya and the Perodicticinae emerging in the early Miocene. Our mitochondrial phylogeny agrees with recent studies based on nuclear data, and supports Euoticus as the oldest galagid lineage and the polyphyletic status of Galagoides. Moreover, we have elucidated phylogenetic relationships for several species never included before in a molecular phylogeny. The results obtained in this study suggest that lorisiform diversity remains substantially underestimated and that previously unnoticed cryptic diversity might be present within many lineages, thus urgently requiring a comprehensive taxonomic revision of this primate group. © 2015 The Linnean Society of London